Evaluation of trained immunity by β‐1, 3 (d)‐glucan on murine monocytes in vitro and duration of response in vivo. Issue 7 (14th March 2017) - Garcia‐Valtanen, Pablo; Guzman‐Genuino, Ruth Marian; Williams, David L; Hayball, John D; Diener, Kerrilyn R
Abstract : The β‐1, 3 (d )‐glucan (β‐glucan) present in the cell wall of Candida albicans induces epigenetic changes in human monocytes resulting in primed macrophages exhibiting increased cytokine responsiveness to reinfection. This phenomenon is referred to as trained immunity or innate immune memory. However, whether β‐glucan can reprogramme murine monocytes in vitro or induce lasting effects in vivo has yet to be elucidated. Thus, purified murine spleen‐derived monocytes were primed with β‐glucan in vitro and assessed for markers of differentiation and survival. Important macrophage cell markers during monocyte‐to‐macrophage differentiation were downregulated and survival enhanced due to partial inhibition of apoptosis. Increased survival and not the β‐glucan training effect explained the elevated production of tumour necrosis factor‐α (TNFα) and interleukin‐6 (IL‐6) induced by subsequent lipopolysaccharide (LPS) challenge. In vivo, 4 days after systemic administration of β‐glucan, mice were more responsive to LPS challenge as shown by the increased serum levels of TNFα, IL‐6 and IL‐10, an effect shown to be short lived as enhanced cytokine production was lost by day 20. Here, we have characterised murine macrophages derived from β‐glucan‐primed monocytes based on their surface marker expression and for the first time provide evidence that the training effect of β‐glucan in vivo declines within a 3‐week period.